Impact of rice export ban on Indian economy - V. R., Renjini; Ajmani, Manmeet Singh; Pal, Barun Deb; Singh, Alka; Nandi, Sukhendu; Naik, P. Bhargav; Naorem, Yoihenba; Mazumder, Chiranjit; Rao, Ch. Srinivasa (Indian Council of Agricultural Research, 2025)
In India, rice is an important crop that provides livelihood opportunity for millions of farmers and ensures food security for the 1.4 billion population. India also contributes 25 percent of global rice production and 40 percent of global rice exports, exporting 16 percent of its domestic rice production (FAO 2022). On the other hand, delayed onset of monsoon, extreme weather events, and weather variability significantly affect rice production and the domestic price of rice in the country (Palanisami et al. 201 7; Bowden, Foster, Parkes 2023). In response to this situation, policymakers frequently reassess export strategies to ensure adequate domestic supply and to control price fluctuations. Given India's significant contribution to the global rice market, any change in rice trade policy to stabilize the domestic rice market in India will affect the global supply chain of rice and the livelihood of lndian farmers. In 2022/2023, in an effort to control rice prices, the government-imposed export restrictions on different varieties of rice such as broken, brown, non-basmati, basmati, and parboiled rice. Figure 1 reveals that total rice exports from India declined from 16.55 lakh metric tons (mt) to 7.58 lakh mt between July 2023 and November 2023, following the July 2023 ban on non-basmati white rice exports. In August 2023, exports of non-basmati white rice declined sharply from 3.81 lakh mt to 0.40 lakh mt, and exports remained negligible until the ban was lifted in February 2024. Parboiled rice also saw a decline, though it was less severe due to selective export allowances. Exports began recovering from early 2024, driven by basmati and parboiled rice. This recovery aligned with India's October 2024 decision to remove the 20 percent export duty on parboiled rice. India's global market share dropped from 35.48 percent in 2022 to 30.46 percent in 2023, creating opportunities for other major rice -exporting countries. Vietnam saw an increase in its exports from 10.52 percent of global share to 11.23 percent, while Pakistan's share rose from 7.75 percent to 8.39 percent. Thailand maintained a steady presence at around 15 percent and the US share rose marginally from 5.62 percent to 5.87 percent. These shifts highlight how India's policy decision disrupted global trade patterns, benefitting competing exporters and altering the international rice market dynamics. Even so, the economywide impact of these restrictions on the Indian economy remains underexplored. While the government aims to maintain domestic price stability, it is unclear how effectively the export ban shields consumers from inflation and how this compares to the income losses experienced by exporters and farmers. Questions also persist about the policy's spill over effects on overall market dynamics. In this note, we examine the impact of the rice export ban on GDP (by sector), employment, and household income in India. We also provide insights aimed at helping policymakers balance affordability for consumers with stable incomes for producers.